Paclitaxel Chemotherapy Elicits Widespread Brain Anisotropy Changes in a Comprehensive Mouse Model of Breast Cancer Survivorship: Evidence From In Vivo Diffusion Weighted Imaging - Otto, Lauren D.; Russart, Kathryn L. G.; Kulkarni, Praveen; McTigue, Dana M.; Ferris, Craig F.; Pyter, Leah M. (Frontiers in Oncology, 2022)
Breast cancer is one of the most common diseases in the United States with 1 in 8 women developing the disease in her lifetime. Women who develop breast cancer are often postmenopausal and undergo a complex sequence of treatments including surgery, chemotherapy, and aromatase inhibitor therapy. Both independently and through potential interactions, these factors and treatments are associated with behavioral comorbidities reported in patients (e.g., fatigue), although the underlying neurobiological mechanisms are poorly understood. Currently, brain imaging is the most feasible way to assess neurobiology in patients. Indeed, breast cancer patients display alterations in white matter connections and chemotherapy is associated with decreased white and gray matter in the corpus callosum and cortex as well as decreased hippocampal volume. However, imaging in breast cancer rodent models is lacking, impeding translation of the mechanistic neurobiological findings made possible through modeling. Furthermore, current rodent models of breast cancer often lack the complexity of typical multimodal breast cancer treatments, thereby limiting translational value. The present study aimed to develop a comprehensive model of post-menopausal breast cancer survival using immunocompetent ovariectomized mice, including an orthotopic syngeneic tumor, surgical tumor removal, chemotherapy, and then aromatase inhibitor therapy. Using this model, we systematically investigated the cumulative effects of chemotherapy and hormone replacement therapy on neurostructure and behavior using diffusion weighted imaging, open field test, and spontaneous alternation test. Our previous findings, in a simplified chemotherapy-only model, indicate that this regimen of chemotherapy causes circulating and central inflammation concurrent with reduced locomotor activity. The current study, in the more comprehensive model, has recapitulated the peripheral inflammation coincident with reduced locomotor activity as well as demonstrated that chemotherapy also drives widespread changes in brain anisotropy. Validating the clinical relevance of this comprehensive rodent breast cancer model will allow for additional neurobiological investigations of the interactions among various cancer components associated with behavioral comorbidities, as well as the relationship between these mechanisms and neurostructural imaging changes that can be measured in cancer patients.